Vulnerable Habitats Alter African Meliponine Bee's (Hymenoptera: Apidae) Assemblages in an Eastern Afromontane Biodiversity Hotspot. (25th May 2017) - Bobadoye, Bridget O; Ndegwa, Paul N; Irungu, Lucy; Fombong, Ayuka T
Habitat degradation has over time formed synergy with other factors to contribute to dwindling populations of both fauna and flora by altering their habitats. The disturbance of natural habitats affects the diversity of both vertebrates and invertebrates by altering both feeding and nesting sites for which organisms are known to depend on for survival. Little is known of the extent to which vulnerable habitats could shape the diversity of most indigent pollinators such as African meliponine bee species in tropical ecosystems. This study was conducted to determine how disturbance could shape the natural occurrence of African meliponine bee species in different ecological habitats of Taita Hills, leading to changes in their diversity. A total of four species depicted by the Renyi diversity profile was recorded in five of the six main habitat types surveyed, and a further extrapolation with Shannon index ( E H ) also predicted the highest species richness of 4.24 in a deciduous habitat type. These meliponine bee species ( Hypotrigona gribodoi, Hypotrigona ruspolii, Meliponula ferruginea (black), and Plebeina hildebrandti ) were observed to be unevenly distributed across all habitats, further indicating that mixed deciduous habitat was more diverse than acacia-dominated bush lands, grasslands, and exotic forest patches. Geometric morphometrics categorized all four meliponine bee species into two major clusters—cluster 1 ( H gribodoi, H ruspolii, M ferruginea (black)) and cluster 2 ( P hildebrandti )—and further discriminated populations against the 4 potential habitats they are likely to persist or survive in. Each habitat appeared to consist of a cluster of subpopulations and may possibly reveal ecotypes within the four meliponine populations. This has revealed that unprecedented conversions of natural habitats to agroecosystems are a key driving factor causing increased habitat isolation and vulnerability in this Afromontane region which may potentially distort local assemblages of native pollinators, such as meliponine bee species.